2019
DOI: 10.1155/2019/3690419
|View full text |Cite
|
Sign up to set email alerts
|

Ontology‐Based Representations of User Activity and Flexible Space Information: Towards an Automated Space‐Use Analysis in Buildings

Abstract: Space-use analysis offers quantitative and reliable references to support architects’ decision-making regarding the planning and design of flexible spaces. To allow for automated space-use analyses of such flexible space, it is imperative to create activity and space ontologies that offer systematic and explicit forms representing user activities and the spaces in which they occur. Therefore, this study extends the current research on activity ontologies in order to capture flexible space-use patterns for user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In terms of technology, research on the application of BIM was found that used virtual geometric data to perform numerical calculations such as pedestrian spatial experience according to specific time and place [93], pedestrian evacuation simulations [94], occupancy modelling using a multi-objective optimization algorithm and the queuing approach [95,96] and analyzing the use of space within buildings [97]. Other technology-related papers were found, where a geographical information system (GIS) was used to study built environments, which led to the use of space syntax metrics to observe pedestrian volume [98] and information and communication technologies were applied in a smart city to search for determining factors that allow networking in public spaces [99].…”
Section: City Servicesmentioning
confidence: 99%
“…In terms of technology, research on the application of BIM was found that used virtual geometric data to perform numerical calculations such as pedestrian spatial experience according to specific time and place [93], pedestrian evacuation simulations [94], occupancy modelling using a multi-objective optimization algorithm and the queuing approach [95,96] and analyzing the use of space within buildings [97]. Other technology-related papers were found, where a geographical information system (GIS) was used to study built environments, which led to the use of space syntax metrics to observe pedestrian volume [98] and information and communication technologies were applied in a smart city to search for determining factors that allow networking in public spaces [99].…”
Section: City Servicesmentioning
confidence: 99%
“…In other sectors beyond these, MCDM is the only dominant decision-making method identified including in Energy [6,52], Automotive [53,54], Manufacturing [55,56], PSS [57,58] and Supply Chain [59]. In all these latter sectors, it perhaps suggests that the emergent appreciation of the complex dynamics and the need for tools that cope with it are the drivers towards this trend.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…It is, however, vital that decision making accounts for this vagueness to better represent the dynamics and improve the rigour of the results. Recently, many MCDM and Hybrid techniques have applied the fuzzy sets as a way of addressing this [50,59,89,92]; while Grey numbers have also been used [74].…”
Section: Consistency Sensitivity and Reiterationmentioning
confidence: 99%
“…This is because individuals in hospitals are highly responsive to the physical conditions of the building [8]. In contrast to conventional spaces, hospitals' elastic spaces are more effective at aligning user activities with the spatial entity [9], thereby enhancing adaptability. This approach, which enhances architectural resilience through flexibility, can significantly improve user adaptability [10].…”
Section: Introductionmentioning
confidence: 99%